Fostering Students' Engagement in EFL Classroom Case Study of Master I EFL Students at Mohammed Cherif Messaadia University - Souk Ahras - ABADLIA Wafa (My University, 2022)
Abstract: Fostering students' engagement in EFL teaching and learning offers a number of mechanisms considered focal in making a successful EFL classroom. Fostering this engagement is to give sense and credebility to the cognitive, emotional and behavioral efforts students' show in the learning process. In order to deduce the useful strategies used by the teacher to foster students' engagement, and because it is the source of the students' autonomy, more precisely this research is destined to Master I EFL students and teachers who try to engage their students actively. This research dealt with a questionnaire destined to both students and teachers to find out their opinions and challenges about how to foster students' engagement inside the classroom, emphesizing on the activites suggested by the teacher to emplement the meaning of engamement as a commitment. In the end, some educational considerations were suggested regarding this topic.